Factors influencing employee retention among workers in KPJ Bandar Maharani Specialist Hospital / Azrul Amri Rosini - Rosini, Azrul Amri (Faculty of Business and Management, 2019)
The main objective for this study is to measure the factors influencing employee retention among workers in KPJ Bandar Maharani. The employee retention element is form under three main dimensions which are teamwork, trust and loyalty, and perceived organizational support. Meanwhile, the dependent variable to be measured under this concept is employees' retention. Then, the researcher's sampling design is non-probability sampling which is convenience sampling method with 150 questionnaires were distributed to the employees within the given time period. Data were collected and evidences are being processed by using Statistical Package for Social Science (SPSS) program. The findings analysis includes descriptive analysis, reliability testing, correlation and multiple regression analysis. The outcome of multiple regression analysis showed that teamwork is the only item that has a positive significant impact on employee retention while the other two, trust in organization and perceived organizational support are not significant. Recommendation and direction for future studies were discussed in this study.